2018
DOI: 10.1039/c8cy01374h
|View full text |Cite
|
Sign up to set email alerts
|

Group 4 permethylindenyl constrained geometry complexes for ethylene polymerisation catalysis

Abstract: The synthesis and characterisation of six permethylindenyl constrained geometry complexes is reported. Slurry phase ethylene polymerisation studies demonstrate that activities increase with increasing electron donating character of the amido fragment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 35 publications
1
22
0
Order By: Relevance
“…AMOST LDH, that is, NiFeCO32/normalA has a higher surface area in comparison to its conventional analogue 50 and surfactant treated LDH, that is, NiFe‐DDS has very higher basal spacing than conventional NiFe 51 . It might be the reason for the exhibited superiority in the thermal property of the resultant polymer because of uniformly disperse LDH in the polymer matrix 52,53 . The thermal degradation stability of EP/NiFe polymer composite based on the anion can be expressed in ascending order as neat EP<NO32<CO32<DDS<CO32/normalA.…”
Section: Resultsmentioning
confidence: 99%
“…AMOST LDH, that is, NiFeCO32/normalA has a higher surface area in comparison to its conventional analogue 50 and surfactant treated LDH, that is, NiFe‐DDS has very higher basal spacing than conventional NiFe 51 . It might be the reason for the exhibited superiority in the thermal property of the resultant polymer because of uniformly disperse LDH in the polymer matrix 52,53 . The thermal degradation stability of EP/NiFe polymer composite based on the anion can be expressed in ascending order as neat EP<NO32<CO32<DDS<CO32/normalA.…”
Section: Resultsmentioning
confidence: 99%
“…[28] Solid polymethylaluminoxane (sMAO) is an insoluble form of oligomeric MAO that has recently been exploited as a solid support for metallocene pre-catalysts in slurry-phase olefin polymerisation. [7,[31][32][33] It is an oligomeric product of the incomplete hydrolysis of AlMe3 (TMA) and consists of (AlMeO)n, where n = 6-30 monomer units. [34] The key advantage of sMAO as a metallocene support is that it can act as a bifunctional support and activator without further modification.…”
Section: Introductionmentioning
confidence: 99%
“…10 We have recently reported the laboratory scale synthesis and detailed characterisation of sMAO, 11 and demonstrated its function as a solid-phase support, scavenger and activator in slurry-phase ethylene polymerisation. [12][13][14] Observed activities are significantly higher than for other supports; for example sMAO-rac-ethylenebis(1-permethylindenyl)zirconium dichloride is at least three times more active than its silicasupported MAO counterpart (5365 vs. 1649 kg PE mol Zr À1 h À1 bar À1 respectively). 15,16 Furthermore, we have shown that reaction of sMAO with tris(pentafluorophenyl)borane or pentafluorophenol produces highly active modified-sMAO supports which show enhanced polymerisation activity with both rac-ethylenebis(1-indenyl) zirconium dichloride, rac-(EBI)ZrCl 2 , 17 and a range of unsymmetrical ansa-bridged permethylindenyl complexes.…”
Section: Introductionmentioning
confidence: 87%